Enrichment of rare earth elements from coal and coal by-products by physical separations. (15th July 2017) - Lin, Ronghong; Howard, Bret H.; Roth, Elliot A.; Bank, Tracy L.; Granite, Evan J.; Soong, Yee
Graphical abstract: Highlights: Enrichment of rare earth elements (REE) from coal and coal by-products. Particle size, magnetic and density (float-sink) separations were investigated. Density separation showed the highest enrichment of REE. Elemental analysis suggests that REE are associated with the Al/Si group. A combination of physical separation methods is recommended for REE enrichment. Abstract: Rare earth elements (REE) are of strategic importance because they find numerous applications in various sectors of the global economy. The concern about the REE supply challenge has led to increasing interest and research in the recovery of REE from end-of-life products and secondary sources such as coal and coal by-products. The work reported here was focused on examining the technical feasibility of physical separation techniques for the enrichment of REE from coal and coal by-products. Particle size, magnetic and density separations were performed on coal, coal ash, clay and shale samples. It was found that the samples responded to particle size separation differently. For all ash samples, higher REE concentrations were found in the finer fractions. For the clay and shale samples, however, the REE concentrations decrease as the particle size reduces possibly because RE minerals were not effectively released by grinding. Magnetic separation showed that REE are enriched in non-magnetic fractions for all ash samples. All samples responded similarly to density separation. Among the three methods, density separation showed the highest enrichment of REE. A combination of these methods is recommended. Finally, correlations between elements were demonstrated, which leads to the classification of three groups containing mainly Al/Si, Fe and Ca, respectively. REE are strongly associated with the Al/Si group.